Preparação de Amostras de Radiocarbono e Aplicações de AMS em Arqueologia e Geologia Marinha - Macario, Kita Chaves Damasio (2003)
This work presents the implantation project of a sample preparation laboratory for radiocarbon samples at the Physics Institute of Universidade Federal Fluminense, to be measured by Accelerator Mass Spectrometry. A twelve-month apprenticeship was realized at the Purdue Rare Isotope Measurement Laboratory PRIME Lab in Indiana, United States. During this period, samples from Archaeology and Geosciences research projects were prepared. The sample preparation and measurement techniques are described, as well as the calculations and corrections for obtaining a given natural carbon sample age. The main results of the research projects involved in this thesis were the reevaluation of pre-historical settlements chronology on the Brazilian Coast and the intermittence of this occupation. It was also determined the Brazilian Continental Slope sedimentation rate in the Campos basin and its relation to sea level fluctuations was studied.